Strategi Dan Pengembangan Wisata Alam Gomara Desa Simonis Kecamatan Aek Natas, Kabupaten Labuhanbatu Utara, Provinsi Sumatera Utara - Setianingsih, Rita Margaretha (Tourism, Hospitality And Culture Insights Journal, 2023)
This research aims to determine the aspects involved in planning tourism areas in the context of appropriate tourism strategies to achieve successful tourism in the Gomara natural tourism area, Simonis Village, Aek Natas District, North Labuhanbatu Regency. The model for finding strategic tourism planning uses the SOAR (Strength, Opportunity, Aspirations and Results) Model, as another alternative to SWOT analysis, this model is a combination of SWOT and Appreciative Inquiry (AI) strategies introduced by Jacqueline M. Stavros. This model focuses on involving all stakeholders and all implementation integrity, to obtain data about Strengths, Opportunities, Aspirations and Results to be achieved in determining the strategy and development of Gomara natural tourism. In this research, descriptive-analytic methods have been used, also library data, semi-structured interview methods and survey methods have been used to collect data. The statistical population of this study includes residents of Aek Natas Village, the Regional Government, NGOs related to Gomara natural tourism, Simonis Village, Aek Natas District, North Labuhanbatu Regency and visiting tourists. The research results show that there are great strengths and excellent opportunities for Gomara natural tourism, Simonis Village, Aek Natas District, North Labuhanbatu Regency. To achieve this aspiration. The government, NGOs, investors and, institutional elements, and local communities must have good collaboration to create a comprehensive tourism plan for Gomara natural tourism, Simonis Village, Aek Natas District, North Labuhanbatu Regency. such as: creating promotional strategies for the uniqueness and richness of tourist attractions, holding cultural festivals and exhibitions, designing websites, educating local people to make unique handicrafts as icons.